How are adults with capacity-affecting conditions and associated communication difficulties included in ethically sound research? A documentary-based survey of ethical review and recruitment processes under the research provisions of the Mental Capacity Act (2005) for England and Wales. Issue 3 (31st March 2022) - Bunning, Karen; Jimoh, Oluseyi Florence; Heywood, Rob; Killett, Anne; Ryan, Hayley; Shiggins, Ciara; Langdon, Peter E
Abstract : Objectives: This study aimed to determine the characteristics of ethical review and recruitment processes, concerning the inclusion of adults with capacity-affecting conditions and associated communication difficulties in ethically sound research, under the provisions of the Mental Capacity Act (MCA, 2005) for England and Wales. Design: A documentary-based survey was conducted focusing on adults with capacity-affecting conditions and associated communication difficulties. The survey investigated: (1) retrospective studies during the implementation period of the MCA (2007–2017); (2) prospective applications to MCA-approved Research Ethics Committees (RECs) during a 12-month period (2018–19); (3) presentational and linguistic content of participant information sheets used with this population. Setting: Studies conducted and approved in England and Wales. Sample: Studies focused on adults with the following capacity-affecting conditions: acquired brain injury; aphasia after stroke; autism; dementia; intellectual disabilities; mental health conditions. The sample comprised: (1) 1605 studies; (2) 83 studies; (3) 25 participant information sheets. Primary and secondary outcome measures: The primary outcome was the inclusion/exclusion of adults with capacity-affecting conditions from studies. The secondary outcome was the provisions deployed to support their inclusion. Results: The retrospective survey showed an incremental rise in research applications post-MCA implementation from 2 (2012) to 402 (2017). The prospective survey revealed exclusions of people on the bases of: 'lack of capacity' (n=21; 25%); 'communication difficulties' (n=5; 6%); 'lack of consultee' (n=11; 13%); and 'limited English' (n=17; 20%). REC recommendations focused mainly on participant-facing documentation. The participant information sheets were characterised by inconsistent use of images, typography and layout, volume of words and sentences; some simplified language content, but variable readability scores. Conclusions: People with capacity-affecting conditions and associated communication difficulties continue to be excluded from research, with recruitment efforts largely concentrated around participant-facing documentation. There is a need for a more nuanced approach if such individuals are to be included in ethically sound research.